Social distancing and mental health two years into a global pandemic: a sequential exploratory mixed-methods investigation in Hong Kong - Sau Fong Leung; Yim Wah Mak; Grace W K Ho; Kwan Ho Wong; Robin K H Kwok; Alice Yuen Loke (BMJ Open)
Introduction The COVID-19 pandemic has led to the implementation of social distancing measures on an unprecedented scale, but their impacts on the mental health of the general public, especially in places with strict and prolonged restrictions, are not well understood. This study explored the Hong Kong public’s views on social distancing measures that were implemented approximately two years into the pandemic and examined how these perceptions influence their stay-at-home motivation and mental health based on Protection Motivation Theory (PMT).Design A two-phase sequential exploratory mixed-methods study was conducted.Setting Data were collected as part of a larger study of a universal online public health campaign in Hong Kong.Participants First, qualitative interviews with 26 participants from diverse backgrounds explored their views on COVID-19 and social distancing measures. Subsequently, a quantitative online survey of 1025 participants from the general population examined the relationship between PMT constructs, stay-at-home motivation, and mental health.Outcome measures Mental health and PMT constructs, including protective motivation, perceived severity, perceived vulnerability, self-efficacy, response cost, and response efficacy.Results The qualitative results identified three themes: ‘the inescapable and unpredictable nature of COVID-19’, ‘stay-at-home impacts all facets of life’, and ‘the realities and challenges of social distancing during a pandemic’. Subsequently, quantitative findings showed that most PMT constructs, such as perceived severity (ß=0.21, 95% CI=0.15–0.27), perceived vulnerability (ß=0.24, 95% CI=0.18–0.30), self-efficacy (ß=0.27, 95% CI=0.20–0.34) and response efficacy (ß=0.09, 95% CI=0.02–0.15), were associated with stay-at-home motivation (all p<0.01), except for response cost. Higher perceived severity (ß=1.42–1.74), perceived vulnerability (ß=0.93–1.36), and response cost (ß=1.29–1.64) were associated with poorer mental health.Conclusion This study examined the public perceptions and experiences of strict and prolonged social distancing measures two years into a global pandemic. The findings highlighted the significance of using the PMT model to understand the factors influencing stay-at-home intentions and their mental health during the pandemic. The findings provide valuable insights to guide the development and implementation of future public health interventions.